Intellectual legacy of second constitutional period's in the hundredth anniversary - Gündüz, Mustafa (My University, 2009)
The Declaration of Second Constitutional Monarchy in 1908 is one of the most important events in the Turkish political, social and cultural life. This event is known as a revolution. After this time, state and social life developed different area and in the way of modernization has been significant way. Besides fundamental changes in state administration press, army, education, health and communication mechanism has begun to change radically. This change has created the infrastructure of modern Turkey Republic. Although the researches are done on a different wing Second Constitution, researches that covering of aspects of the lack of research is clear. In this paper, to understand the different aspects of second constitutional period, issues are based on academic studies on this period as a whole will be reviewed. Literature method was used in this paper.
100. Yilinda II. mesrutiyet'in entellektüel mi?rasi
Keywords: Economy; Education; Intellectual legacy; Late ottoman period; Modernization; Politics; Republic; Second constitutional monarchy